2015
DOI: 10.4238/2015.june.11.12
|View full text |Cite
|
Sign up to set email alerts
|

A simplified genomic DNA extraction protocol for pre-germination genotyping in rice

Abstract: ABSTRACT. Genotyping is a critical step for molecular markerassisted selection in rice. Rice genomic DNA samples for genotyping are typically isolated from living tissues such as seedlings. This requires the germination of all candidate seeds and extraction of DNA from the seedlings. Currently, an ideal individual is selected from a very large number of plants, which is time-and labor-consuming, requiring several transplantations of materials and sampling processes. In this study, we developed a simplified gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The need of liquid nitrogen during grinding step has been eliminated by many workers using soft tissues such as flower petals or young leaves (Khan et al, 2004), cold and heat shock treatments, (Biswas and Biswas, 2011) alcohol fixation (Sharma et al, 2003;Sharma et al, 2010). (Duan et al, 2015;Ibemhal et al, 2015). Here, we developed an easy, fast, inexpensive method to isolate high quality genomic DNA from mungbean eliminating the use of hazardous chemical phenol and expensive reagents like proteinase K and liquid nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…The need of liquid nitrogen during grinding step has been eliminated by many workers using soft tissues such as flower petals or young leaves (Khan et al, 2004), cold and heat shock treatments, (Biswas and Biswas, 2011) alcohol fixation (Sharma et al, 2003;Sharma et al, 2010). (Duan et al, 2015;Ibemhal et al, 2015). Here, we developed an easy, fast, inexpensive method to isolate high quality genomic DNA from mungbean eliminating the use of hazardous chemical phenol and expensive reagents like proteinase K and liquid nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…The rice DNA extraction methods typically use seedlings or leaves and require fine grinding of the tissue materials using liquid nitrogen. Different methods of DNA isolation have been reported in many studies (Ahmadikhah, 2009, Aliyu et al, 2013Fouladvand et al, 2013 andDuan et al, 2015). references Ahmadikhah, A.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Although efficient DNA extraction procedures and commercial kits are readily available for rice leaves as the starting material, very few studies have been conducted to establish DNA fingerprinting protocols for rice caryopses and flour (Mutou et al, 2014). Two protocols have been established for DNA extraction from rice seeds by Duan et al, (2015) and from half-cut rice seeds of the varieties Nipponbare (O. sativa Japonica) and Junyou522 (O. sativa Indica) by Liang et al, (2016). However, none of these studies used common varieties found in Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%